Graphing story problems - Cocca, Lisa Colozza, 1957-; Petelinsek, Kathleen (Ann Arbor, Mich. : Cherry Lake Pub., 2013)
Introduces graphs, describes the different types, and discusses how to obtain data and use it to create a graph
What are graphs? -- Graphing beads -- Graphing miles -- Graphing fish -- Graphs are fun
Includes bibliographical references (p. 23) and index
005-007
Grades K to 3
Keywords: Word problems (Mathematics) -- Graphic methods -- Juvenile literature; Mathematics -- Graphic methods -- Juvenile literature